Human resource management, social innovation and technology / edited by Tanya Bondarouk [and] Miguel R. Olivas-Luján. - Bondarouk, Tanya, 1967-; Olivas-Lujan, Miguel R. (Advanced series in management (Unnumbered), 2014)
To meet the requirements of globalization, diversity, 'war for talent', and fast technological developments, human resource management (HRM) should allow a greater amount of flexibility and innovation in policies and practices. In order for this to happen, HRM needs to be modernized by replacing inefficient and unsustainable practices and forms with flexible, sound, and pioneering ones, crossing inter- and intraorganizational boundaries. This book discusses innovation of HRM from two ends of one continuum: at one end, human resources practices and policies should be designed to support innovative organizational members, the creation of new ideas, an innovative organizational climate, and enlargement of the innovation capacity of organizations; at the other end, the HRM function evolves through applying new structures and new channels for delivery of the human resources practices, and through involving new agents in the management of human resources. --